1994
DOI: 10.1002/jhrc.1240170414
|View full text |Cite
|
Sign up to set email alerts
|

High resolution gas chromatographic determination of the atmospheric reactivity of engine‐out hydrocarbon emissions from a spark‐ignited engine

Abstract: SummaryThe reactivities of engine-out exhaust hydrocarbon (HC) emissions in photochemical smog formation have been determined for three fuels (isooctane, an aromatic blend, and a gasoline) in a single-cylinder, spark-ignited engine. High resolution capillary GC was used to determine the mole fractions of the exhaust hydrocarbon species. Temperature programmed chromatography on a single capillary column was sufficient to separate the major exhaust species. A library of approximately 160 hydrocarbon species was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…These results are certainly very interesting. However, the observations and conclusions drawn in their paper are in large measure identical (with certain exceptions) to those presented earlier in a series of publications from the Ford Motor Co., [2][3][4][5][6] which have not been cited by the authors. For this reason, I believe it is important to discuss briefly the Ford results and to compare them to this Journal paper.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…These results are certainly very interesting. However, the observations and conclusions drawn in their paper are in large measure identical (with certain exceptions) to those presented earlier in a series of publications from the Ford Motor Co., [2][3][4][5][6] which have not been cited by the authors. For this reason, I believe it is important to discuss briefly the Ford results and to compare them to this Journal paper.…”
supporting
confidence: 78%
“…(3) The abstract of Kaiser et al 1993 4 states, "1,3-butadiene (emission) is significant for the straight-chain terminal olefin (fuels), 1-butene and 1-hexene, but is much less important for the highly-branched olefin diisobutylene." (4) Although not discussed specifically in Kaiser and Siegl 1994, 5 Table 1 in that article shows that methacrolein is present in the engine-out exhaust from pure isooctane fuel at a level approximately 3-4 times larger than from the gasoline fuel in Table 3, which contains 11% isooctane. (5) The abstract from Kaiser et al 1994 6 reports, "The primary (non-fuel) exhaust hydrocarbon species from MTBE combustion is identified as isobutene."…”
mentioning
confidence: 95%
“…In addition, samples were withdrawn through another heated sample line into evacuated Pyrex flasks from a port immediately after the exhaust plenum. These samples were analysed by a gas chromatograph (GC-FID/MS, gas chromatograph± flame injection detector/mass spectrograph) to determine the mole fractions of individual HC species (C 1 to C 12 ) by a technique described earlier [13]. These gas chromatograph (GC) samples were taken at reduced pressure (<80 torr) to avoid any possibility of water condensation.…”
Section: Methodsmentioning
confidence: 99%
“…The source of the unburned HC participating in the post-flame oxidation is the cylinder crevice volume during the expansion stroke for SI combustion and the over-lean or overrich fuel-air mixture for diesel combustion (Heywood, 1988). According to a post-flame oxidation study of a SI engine, as the post-oxidation degree increases, the fraction of fuel alkanes/THC decreases because fuel alkanes are oxidized into smaller HCs (Bohac et al, 2004;Kaiser et al, 1994). Alkenes/fuel alkanes and methane/THC fractions increase because of incomplete oxidation (Kaiser et al, 1994).…”
Section: Post-flame Oxidation and Ozone Forming Potentialmentioning
confidence: 99%
“…Moreover, the aspect of post-flame oxidation that a lot of SI combustion studies have reported on (Kaiser and Siegl, 1994;Bohac et al, 2004) may provide a better understanding of PCI combustion because PCI has a relatively higher expansion gas temperature due to the later fuel injection timing (compared to conventional combustion) and available oxygen during expansion. Postflame oxidation of unburned HCs results in an increase of the amount of partially oxidized HC that is converted into smaller derivatives; further oxidation reactions may be frozen below certain gas temperatures.…”
Section: Introductionmentioning
confidence: 98%